Diffusion and distribution of deuterium in scandium deuteride thin films under irradiation of deuterium ion beam - Wang, Tao (2018)
Scandium deuteride (ScDx) thin films, as an alternative target for deuterium-deuterium (D-D) reaction, are a very important candidate for detection and diagnostic applications. Albeit with their superior thermal stability, the ignorance of the stability of ScDx under irradiation of deuterium ion beam hinders the realization of their full potential. In this report, we characterize ScDx thin films with scanning electron microscopy (SEM) and X-ray diffraction (XRD), Rutherford backscattering spectroscopy (RBS) and elastic recoil detection analysis (ERDA). We found with increased implantation of deuterium ions, accumulation and diffusion of deuterium are enhanced. Surprisingly, the concentration of deuterium restored to the value before implantation even at room temperature, revealing a self-healing process which is of great importance for the long-term operation of neutron generator.